Using the 3D digital orchid design program to cultivate digital talents. Issue 2 (23rd February 2017) - Weng, Ting-Sheng
ABSTRACT: As the digital animation industry becomes increasingly important, the industrial demand for digital technology talents will certainly increase. However, under a short supply of talents, it is necessary to cultivate digital technology talents. This study developed a 3D orchid design program using 3ds MAX technology, which allows students to construct the appearance of an orchid. The research results can be used as reference for the study of orchids, and for use in digital archives, in order to improve the competitiveness of Taiwan's orchid cultivation industry in international society. Using the animation technology of 3ds MAX for teaching can enhance teachers' teaching performance and students' learning effects, and facilitate the cultivation of digital technology talents. The supply of the required talents for the industry, as well as an effective combination of education and practice, can promote the successful transformation of traditional industries in Taiwan and improve the overall industrial competitiveness. GRAPHICAL ABSTRACT: